A synchronic and diachronic examination of the ex-situ term focus construction in Fulfulde of Fuuta Jaloo - Apel, Viktoria (AAeO - Afrikanistik-Aegyptologie-Online, 2015)
The present paper describes the most frequent construction type for term focus in Fulfulde of Fuuta Jaloo (Guinea) and discusses hypotheses for its synchronic analysis and its diachronic development. Although this dialect has around 3 million speakers, little attention was paid to it in linguistic research in spite of the significant differences it shows to its neighboring dialects. After describing the ex-situ term focus construction in detail, I will argue that we are not dealing with a cleft sentence as it is assumed in the Senegalese variety, but rather with a cleft-like structure. Subsequently I will discuss two hypotheses: 1) a grammaticalization of a former cleft towards its present-day focus construction, and 2) the identificational function of the focus clause and the backgrounding function of the out-of-focus clause as a driving force for the development of the construction. The arguments for both scenarios being convincing, no hypothesis can be clearly preferred over the other one.